Congenital microvillous atrophy: specific diagnostic features. Issue 2 (February 1985) - Phillips, A D; Jenkins, P; Raafat, F; Walker-Smith, J A
Abstract : Proximal small intestinal and colonoscopic mucosal biopsies from two children with the intractable diarrhea of infancy syndrome were examined by electron microscopy. Microvillous involutions were found in the small and large bowel of both patients. We suggest that this is a specific diagnostic finding for congenital microvillous atrophy, a distinct disorder within the intractable diarrhoea syndrome which has an extremely poor prognosis.